Mild Prolongation of Prothrombin Time Does Not Affect the Safety and Prognosis of Transjugular Intrahepatic Portal Shunt: Based on Real-World Data - Bai, Yaowei; Liu, Jiacheng; Chen, Yang; Yang, Chongtu; Wang, Yingliang; Wang, Chaoyang; Ju, Shuguang; Zhou, Chen; Huang, Songjiang; Li, Tongqiang; Yao, Wei; Yao, Jinghong; et al. (Turkish Journal of Gastroenterology, 2023)
Background/Aims: The aim was to investigate the safety and prognosis of transjugular intrahepatic portal shunt in patients with mildly prolonged prothrombin time. Materials and Methods: Two hundred fifty-three patients with portal hypertension who received transjugular intrahepatic portal shunt from November 2015 to May 2021 in Wuhan Union Hospital were retrospectively selected. According to the preoperative prothrombin time, they were divided into 2 groups: 126 patients in the non-clinical significance group (prothrombin time prolongation <3 seconds) and 127 patients in the clinical significance group (3 seconds ≤ prothrombin time prolongation <6 seconds). A line chart of postoperative liver and kidney function was drawn, and Kaplan–Meier curve was used to analyze and compare the prognosis of the 2 groups. Results: Transjugular intrahepatic portal shunt was successfully performed in all patients; the technical success rate was 100%, and no puncture-related complications occurred during perioperative period. The mean preoperative prothrombin time was 14.9 ± 0.7 seconds in the non-clinical significance group and 17.2 ± 0.8 seconds in the clinical significance group. During follow-up, 1-year stent dysfunction rates in the non-clinical significance group and clinical significance group were 3.5% and 6.9%, respectively, with no statistically significant difference (hazard ratio = 0.77, 95% CI = 0.30-1.93, log-rank P = .575). In addition, there were no significant differences in the cumulative survival rate (log rank P = .255), rebleeding rate (log-rank P = .392), and incidence of hepatic encephalopathy (log-rank P = .404) between the 2 groups. Subgroup analysis of the clinical significance group showed no significant difference in safety and prognosis between the 2 subgroups. Conclusion: Transjugular intrahepatic portal shunt is safe for portal hypertension patients with prothrombin time prolongation <6 seconds. There was no significant difference in prognosis between the non-clinical significance group and the clinical significance group Cite this article as: Bai Y, Liu J, Chen Y, et al. Mild prolongation of prothrombin time does not affect the safety and prognosis of transjugular intrahepatic portal shunt: Based on real-world data. Turk J Gastroenterol. 2023;34(8):873-880.